PENGARUH SKEPTISME PROFESIONAL, KEAHLIAN AUDIT, LINGKUP AUDIT DAN ETIKA TERHADAP KETEPATAN PEMBERIAN OPINI AUDITOR (Studi Empiris Pada BPK Perwakilan Kepualauan Riau di Batam ) - Suryani, Lili; Hanif, Rheny Afriana; ', Kamaliah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The research was conducted to determine the influence of Skeptisme Profesional, audit skills, audit scope and ethics to the In Giving Up Financial Statements Audit Opinion. In this research, researchers examined consideration granting audit opinion on the State Audit Board Office (BPK) RI Representative of Kepulauan Riau province by using the independent variables, namely Skeptisme Profesionalisme , audit skills, audit scope and ethics. The population in this research was all auditors who working on State Audit Board Office (BPK) RI Representative of Kepulauan Riau province. The primary data collection method used is the methode of questionnaires distributed to respondent , the sampling technique is by Sensus sampling with total sample of 34 respondents. The data analysis techniques used in this research is the technique of multiple linear regression analysis. The results of hypothesis testing in this research indicate that the variable Skeptisme Profesionalisme, audit skills, audit scope and ethics have significant impact on the prevision of audit opinion. Simultaneously, the variables independence, audit skills, audit scope and ethics and significant impact on the privision of an audit opinion.Keyword : audit opinion, Skeptisme Profesionalisme, audit skills, audit scope, ethics